True Cost Accounting of a healthy and sustainable diet in Italy - Minotti, Bianca; Antonelli, Marta; Dembska, Katarzyna; Marino, Davide; Riccardi, Gabriele; Vitale, Marilena; Calabrese, Ilaria; Recanati, Francesca; Giosuè, Annalisa (Frontiers in Nutrition, 2022)
It is widely upheld that global food systems are unsustainable. Sustainable diets are gaining prominence as key components to entangle global food system challenges as well as to transition towards the pathway of the 2030 Agenda and the SDGs. Hence, sustainable, and healthy diets are at the core of much research with the aim to bring together nutritional adequacy, cultural acceptability, environmental sustainability and economic affordability and shape future consumption patterns. This article contributes to advancing knowledge on sustainable diets by proposing a True Cost Accounting method to assess the cost and impact of the adoption of a more sustainable and healthier diet, using Italy as illustration. The research analyses the complexity of a diet from an environmental, health and socio-economic point of view and defines a new assessment framework that can be replicated and adapted to other contexts. Results show that, in Italy, adoption of a sustainable and healthy diet has 47% lower carbon footprint and 25% lower water footprint than the current diet, while impacting 13% less on the average income and food monthly expenditure. Also, the desirable diet has a 21% lower impact on the sanitary costs related to cardiovascular disease. The study corroborates that the consumption of the desirable diet would provide a total cost saving of 741 EUR per year per capita if we consider its impact on environment, health, and socio-economic costs.